Pengaruh Ukuran Perusahaan, Leverage dan Profitabilitas Terhadap Tax Avoidance Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Hilmi Ikhwan Harahap; Pirma Sibarani; Eli Safrida; Khanti Listya (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2024)
This research aims to empirically prove the influence of company size, Leverage and profitability on Tax Avoidance in non-cyclical consumer sector manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique in this research is the purposive sampling method. The sample in this research consisted of 35 companies and 175 observation data. The data collection technique used in this research is documentation techniques. Data was collected based on annual reports and audited financial reports of non-cyclical consumer sector companies for the period 2018 – 2022 which can be accessed via the official website of the Indonesia Stock Exchange. The data was processed and analyzed using multiple linear regression analysis techniques with SPSS version 25 software. The results of this research show that profitability has a negative effect on Tax Avoidance, while company size and Leverage have no effect on Tax Avoidance.